Risk factors for venous thromboembolism in metastatic colorectal cancer with contemporary treatment: A SEER‐Medicare analysis. (6th February 2022) - Ades, Steven; Pulluri, Bhargavi; Holmes, Chris E.; Lal, Inder; Kumar, Santosh; Littenberg, Benjamin
Abstract: Background: The relationship between metastatic colorectal cancer (mCRC) and venous thromboembolism (VTE) is poorly defined in the modern era. Our objective was to examine impact of putative risk factors including newer treatments and anti‐angiogenic therapy on VTE incidence and survival in a modern older mCRC cohort. Methods: This is a SEER‐Medicare cohort analysis of mCRC patients diagnosed in 2004–2009. Risk factor analysis was conducted using Cox models adjusted for sex, diagnosis age, race, primary tumor location, comorbidity, and prior VTE history, with cancer treatments as time‐varying covariates. Main outcomes were VTE incidence and overall survival. Results: Ten thousand nine hundred and seventy six mCRC cases with mean age 77.9 years (range 65–107), 49.7% women, 83.5% white. There were 1306 VTE cases corresponding to 13.7% incidence at 1 year and 20.3% at 3 years. Independent VTE predictors included female sex (HR 1.27; 95% CI 1.14–1.42), African American race (HR 1.49; 1.27–1.73), prior VTE history (HR 16.3; 12.1–22.1), and right sided cancers (HR 1.16; 1.04–1.29). After adjustment, any therapy and bevacizumab (HR 0.68, 0.58–0.78) in particular were protective. Overall survival was 40.1% (39.4–41.3) at 1 year but improved significantly with any treatment. VTE following diagnosis of mCRC was associated with inferior OS (HR 1.09; 1.02–1.15). Conclusions: In this large contemporary mCRC cohort, effective systemic therapy including anti‐angiogenic treatment was associated with lower VTE risk. Overall survival was poor, and modestly worse if a patient had a VTE at any time during treatment. Abstract : In a large contemporary SEER‐Medicare cohort, the cumulative 1‐year incidence remains high at 14%. Current standard therapies for advanced colon cancer including bevacizumab are associated with lower VTE risk and significant survival gains.